Study on tribological and vibration performance of a new UHMWPE/graphite/NBR water lubricated bearing material - Zhimin, Yan; Xincong, Zhou; Hongling, Qin; Wanying, Niu; Hao, Wang; Kai, Liu; Yumin, Tang (Wear, 2015)
The mixture powder of Ultra-high molecular weight polyethylene (UHMWPE) and graphite was blended into nitrile–butadiene rubber (NBR) to be modified to develop a new kind of compound water lubricated rubber bearing with cost-effective, low-friction performance. In order to study the tribological and vibration performance of the new material, a series of experiments were carried out on the test rig SSB-100. Friction coefficient and vibration characteristics under different working conditions: speed, specific pressure and temperature were acquired and analyzed by torque meter and B&K Pulse. The mechanical physical performance of the compound rubber material SPB-N has reached the requirements of Chinese ship standard CB/T769-2008. The results showed that a better tribological performance of the new material met the U.S. military standard (MIL-DTL-17901C (SH)). Stick-slip effect of the new material was induced with critical speed of 0.27m/s, which showed excellent low-speed performance. Moreover, its friction coefficient reached a minimum value at the speed of 0.54m/s. Local specific pressure of the new material was 0.7MPa. The new composite rubber material was served as a kind of water-lubricated bearing material with excellent all-round performances. •The mechanical physical performance of the material has reached CB/T769-2008.•The friction coefficient is within the prescribed scope of MIL-DTL-17901(C).•The SPB-N bearing shows an outstanding low speed performance.•Local specific pressure of the SPB-N bearing is 0.7MPa.